Pengembangan E-Modul dengan Pendekatan Inkuiri Terbimbing Pada Materi Ekologi dan Perubahan Lingkungan di MAN 2 Jambi - Moralita Chatri; Muhyiatul Fadilah; Vauzia; Ahmad Subari (Postgraduate, University of Mataram, 2022)
The purpose of this study was to produce an E-Module on ecology and environmental change using a guided inquiry approach that is valid, practical, and effective. This type of research is development research using the Plomp model. The development phase of this model begins with the Preliminary research phase, the Development or prototyping phase, and the Assessment phase. The instruments used in this study were validity assessment sheets, practicality assessment sheets, and competency assessment sheets for knowledge, skills, attitudes, motivation, and science process skills. The results showed that the E-Module on ecology and environmental change using a guided inquiry approach based on the expert judgment was very valid with a value of 97.59%. The practicality assessment by the teacher obtained a score of 95.83% with very practical criteria and a student assessment in the field trial (large group evaluation) with a score of 90.45% with very practical criteria. The results of the effectiveness test found that the class using the E-Module on ecology and environmental change with the guided inquiry approach had higher scores than the class that did not use the E-Module, so the use of the E-Module with the guided inquiry approach supplemented with pictures, animations and videos could help students understand the material. It can be concluded that the E-Module on ecology and environmental change with the guided inquiry approach that has been developed is in the category of very valid, very practical, and very effective in improving student learning outcomes.